PSYCHOLOGICAL LEADERSHIP TRAINING OF CRISIS MANAGEMENT - Lefterov , V.O.; Lazor, K.P. (Modern Psychology, 2019)
The necessity of delivering psychological bases of crisis management to leadership is substantiated and psychological recommendations for effective management of leaders have been offered. The author’s vision of the socio-psychological components of the managerial competence of a modern manager is being highlighted: it suggests the introduction into the system of training managers of various categories of psychological training as an innovative technology of forming leaders’ practical skills and capabilities of efficient personnel management. The results of an experimental study of the influence of training on the dynamics of personal and professionally significant qualities of leaders are being presented. A significant positive impact of leadership training on the personal sphere of leaders, increasing of leadership potential and the development of individual psychological qualities that are essential for a modern manager, has been established. Over time, after the training, the level of volitional, leadership qualities has been increased, such as leadership role, self-discipline, purposefulness, and the assessment of their business and personal qualities given by subordinates increases. Psychological training of leadership in the form of training contributes to the development of such necessary qualities of crisis management as stress resistance and the ability for emotional self-regulating.
Keywords: psychological training; crisis management; social and psychological components of a successful leader